ANALISA LINGKUNGAN KERJA DAN KESEHATAN, KESELAMATAN KERJA ( K3) (STUDI KASUS: PT. ASRINDO CITRASENI SATRIA) - Nur, Muhammad (LPPM ITK, 2019)
Asrindo Citraseni Satria is a service company engaged in various projects providing and leasing heavy equipment for various construction activities, providing services to wellbores such asDrilling Rigsand reworking oil wells, providing services on routine service and maintenance of oil wells, as part of corporate services for our clients in the oil and gas industry. Currently the company's drilling project is underway in the Outside and NDD Area (North Duri Development) PT. Chevron Paci ? c Indonesia. The results obtained are that the working environment at the company and the implementation of the health, safety (K3) program are still very weak. This is due to lack of employee awareness and employee non-compliance in carrying out programs that have been designed by the company. Therefore, research on the work environment and health, work safety (K3), from the analysis conducted using the FTA (method, isFault Tree Analysis)known that the factors causing occupational accidents due to human negligence and the scattered environment. Then the solution provided by researchers is that companies are expected to be more stringent in implementing programs that have been designed to improve employee performance and reduce work accidents at ACS companies.   Keywords: FTA (Fault Tree Analysis), Work Accident, Occupational Health and Safety (K3)